Functionality of lyophilized osteoinductive EVs: a mechanistic study - Huang, Chun-Chieh; Kang, Miya; Debnath, Koushik; Leung, Kasey; Raghavan, Vidhath; Lu, Yu; Cooper, Lyndon F.; Gajendrareddy, Praveen; Ravindran, Sriram (Frontiers in Bioengineering and Biotechnology, 2024)
Mesenchymal stem cell derived extracellular vesicles (MSC EVs) possess immense therapeutic potential. Us and others have characterized EV bioactivity mechanistically as well as devised approaches to engineer EVs for regenerative medicine applications. For these advances to be clinically relevant, translational approaches to EV therapeutics need to be evaluated and established. Long-term stability and storage of purified EVs by lyophilization is one of the major hurdles facing translation of EV therapeutics. While current studies have focused extensively on the biophysical characterization of the lyophilized EVs, the functional, mechanistic and in vivo functionality of the EVs has remained understudied. Using functionally engineered osteoinductive EVs developed and characterized in our laboratory, in this study, we have endeavored to compare the functional and mechanistic bioactivity of fresh and lyophilized EVs in vitro and in vivo using dimethyl sulfoxide (DMSO) as a cryoprotectant. Results presented here highlight the ability of DMSO to maintain the functional stability of the engineered EVs in vitro and in vivo and serve as a baseline for its potential in EV therapeutics. Future studies can focus on expanding this knowledge to test other cryoprotectants as well as functionality of lyophilized naïve and engineered EVs in regeneration of multiple other tissues.